2
$\begingroup$

In classic physics, kinetic energy is defined as $$ KE = \frac{1}{2}m v_x^2 + \frac{1}{2}m v_y^2 + \frac{1}{2}m v_z^2 $$ So, by defining $ KE_x = \frac{1}{2} m v_x^2 $ , $ KE_y = \frac{1}{2} m v_y^2 $, $ KE_z = \frac{1}{2} m v_z^2 $, we can know the contribution of each components to the total kinetic energy.

However, in the case of relativistic kinetic energy, its definition is $$ KE = \sqrt{(mc^2)^2+(p_x^2+p_y^2+p_z^2) c^2}-mc^2 $$ Now, partitioning this into each components seems impossible.

Does this mean thinking of "x component" of kinetic energy becomes meaningless in relativistic theory?

$\endgroup$
0
$\begingroup$

I think it would still possible to determine relativistic components in each spacial direction. One would need to know the relative velocities $\beta = \frac{v}{c}$ w.r.t. light for each direction and multiply each component by the x,y, and z Gamma values. $\gamma = \frac{1}{\sqrt(1-\beta^2)}$

$\endgroup$
0
$\begingroup$

What you are looking for is a function of $f(v_i)$ such that $f(v_x) + f(v_y) + f(v_z) = KE$.

In the case of Newtonian physics, $f(v_i) = \frac{1}{2}mv_i^2$.

In the case of special relativity, it is impossible to find any such function.

Proof by contradiction: Suppose that such an $f$ did exist. Now imagine three objects of mass $m$, each with a different velocity:

Object $A$ is stationary. Its kinetic energy, denoted $KE_A$, is equal to $0$. This implies that $f(0)+f(0)+f(0)=0$, and therefore $f(0)=0$.

Object B is traveling in the $x$ direction with velocity $v_x=\frac{3c}{5}$. Therefore it has kinetic energy $KE_B = \frac{1}{4}mc^2$. Together with the result for object A, this implies that $f(\frac{3c}{5}) = \frac{1}{4}mc^2$.

Object C is traveling in both the $x$ direction and the $y$ direction. Its velocity components are $v_x=v_y=\frac{3c}{5}$. Its total velocity is $v = \sqrt{2}\frac{3c}{5}$. We have: $\gamma=\frac{1}{\sqrt{1-\frac{18}{25}}} = \frac{5}{\sqrt{7}}$. Therefore, $KE_C=\frac{5\sqrt{7}-7}{7}mc^2$. However, it must also be true that $KE_c = f(\frac{3c}{5}) + f(\frac{3c}{5}) = \frac{1}{2}mc^2$.

Since these two answers are different, we have a contradiction.

Q.E.D.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.